Strategi Suriah Dalam Mempertahankan Hubungan Diplomasi Dengan Rusia Pada Massa Bassar Al Assad 2011-2015 - Erman Utomo Adi (HI 16 UMY 138, 2016)
*138 A state innatewill try to establish cooperative relations with other state in an effort to resolve domestic problems. Other way, a state will establish an alliance to ease the realization of the states interests. Middle-east as a strategic region, politically and economicaly, has been considered profitable by many state. Many states have tired ti establish a bilateral relationship with middle-eastern states, however, some of middle-eastern states tend to become authoritative and complicated in establishing cooperative relations. Russian came and tried to establish a relationship with Syria by officially acknowledged the Syrian’s independence. A good relationship was established between both countries. However, a political change in Syria led their bilateral relation became However the occurrence of Arab Spring phenomena in middle east, particularly in Syria leads the Russian-Syria relationship became better.